An ultra-wideband polarization conversion metasurface for RCS reduction. Issue 5 (24th March 2022) - Lin, Bao-qin; Huang, Wenzhun; Yang, Yongsheng; Guo, Jianxin; Lv, Lintao; Zhang, Jintao
Abstract : In this paper, a polarization conversion metasurface is proposed, which can realized ultra-wideband circular polarization (CP) maintaining reflection in the frequency range 7.3–28.7 GHz; in addition, when its unit cell structure is rotated by an angle ψ, almost ±2 ψ Pancharatnam-Berry (PB) phase will be generated in its co-polarized reflection coefficient under CP incidence. Thus, base on the polarization conversion metasurface, an ultra-wideband PB 2-dit coding metasurface is further proposed for Radar Cross Section (RCS) reduction. The simulation and experiment results show that the coding metasurface can achieve more than 10 dB RCS reduction in the ultra-wide frequency band 7.2–28.6 GHz under normal incidence with arbitrary polarizations; in addition, when the incident angle is increased to 45 °, the ultra-wideband RCS reduction can still be realized, which shows that the coding metasurface has good stealth performance in X, Ku and K bands, and it is very practical for most airborne radar, fire control radar and imaging radar working in these bands.